Performance diagnóstica da elastografia shear wave na avaliação de nódulos tireoidianos - Morais, Fabíola Prado de (2019)
Introduction: Thyroid nodules are a challenge in clinical practice since several thyroid diseases may manifest as nodules. Many ultrasonography classifications estimate the risk of malignancy of thyroid nodules, such as the Thyroid Imaging Reporting and Data System (TI-RADS) and American Thyroid Association (ATA). Based on the principle of tissue elasticity, thyroid elastography is a non-invasive technological proposal that aims to differentiate benign and malignant thyroid nodules. Objectives: To evaluate the diagnostic performance of shear wave elastography (SWE) for the discrimination of benign and malignant thyroid nodules using cytological analysis, based on The Bethesda System, as the reference standard. Material and methods: 75 thyroid nodules were included in the study. SWE, TI-RADS and ATA ultrasound patterns were performed. We divided the nodules into two groups according to the cytological results (The Bethesda System): group 1 (clinical and sonographic follow-up - benign category) and group 2 (nodules that undergo excision - categories "follicular neoplasm/suspicious for a follicular neoplasm", “suspicious for malignancy” and “malignant”). We evaluated the ability of each technique alone (SWE, TI-RADS and ATA) and combined (SWE + TI-RADS and SWE + ATA) to assess the true diagnosis of the nodule (benign or malignant). A Receiver Operating Characteristic (ROC) curve determined the SWE cutoff. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of each technique (isolated and combined) were also obtained. Results: SWE’s cutoff to predict malignancy was 31.5 kPa. SWE was the most sensitive technique for thyroid nodules evaluation and increased the sensitivity of TI-RADS and ATA ultrasound patterns. Conclusion: The association of SWE with TI-RADS and/or ATA ultrasound patterns may improve the stratification of thyroid nodules risk and reduce invasive procedures.